Clinical characteristics of HIV-infected patients who survive after the diagnosis of HIV infection for more than 10 years in a resource-limited setting - Sasisopin Kiertiburanakul (2018)
A retrospective cohort study was conducted and 129 patients with a diagnosis of HIV infection for more than 10 years were identified. Half the patients were men and mean (standard deviation, SD) age at HIV diagnosis was 33.2 (9.2) years. One third had a diagnosis of AIDS at cohort entry with median (interquartile range, IQR) CD4 counts of 259 (112-430) cells/mm3. All received antiretroviral therapy with median (IQR) current CD4 counts of 502 (363-607) cells/mm3 and 95% had HIV RNA < 50 copies/mL. For adverse events, 28% experienced drug resistance, 27% experienced hospitalization, 59% had dyslipidemia, 35% had creatinine > 1.0 mg/dL, and 5% had glucose > 126 mg/dL. In conclusion, immunological and virological responses can be achieved among patients with a diagnosis of HIV infection for more than 10 years even in a resource-limited setting. Adverse events are common. Preparation for monitoring and management of these adverse events is a crucial part of successful long-term HIV care. © 2012 SAGE Publications.